2013
DOI: 10.1155/2013/793927
|View full text |Cite
|
Sign up to set email alerts
|

PET/MRI Imaging in High-Risk Sarcoma: First Findings and Solving Clinical Problems

Abstract: Simultaneous positron emission tomography (PET) and magnetic resonance imaging (MRI) is a new whole-body hybrid PET/MR imaging technique that combines metabolic and cross-sectional diagnostic imaging. Since the use of MRI in imaging of soft-tissue sarcoma is extremely beneficial, investigation of the combined PET/MRI is of great interest. In this paper, we present three cases and first data. Combined PET/MRI technique can support the process of clinical decision-making and give answers to some meaningful quest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 29 publications
1
16
0
Order By: Relevance
“…This is the first study to systematically evaluate FDG PET/MRI in this setting. Previously, the use of this modality for sarcoma imaging was only mentioned in case reports [11,12,30]. Our study demonstrates that the combined FDG PET/MRI examination is feasible for response assessment in sarcoma.…”
Section: Discussionsupporting
confidence: 54%
See 1 more Smart Citation
“…This is the first study to systematically evaluate FDG PET/MRI in this setting. Previously, the use of this modality for sarcoma imaging was only mentioned in case reports [11,12,30]. Our study demonstrates that the combined FDG PET/MRI examination is feasible for response assessment in sarcoma.…”
Section: Discussionsupporting
confidence: 54%
“…Indications for PET/MR have yet to be evaluated. There are already initial reports describing the use of PET/MR with 18 F-fluorodeoxyglucose (FDG) for imaging of lung cancer [8], lymphoma [9], and neuroendocrine tumors [10] as well as several case reports in sarcoma patients [11,12]. The use of PET/MR for sarcoma staging has not been systematically evaluated, yet [13].…”
Section: Introductionmentioning
confidence: 99%
“…ROC analysis for distant metastasis detection showed a sensitivity of 97.8% and specificity of 100% for PET‐MRI, compared with 94.4% and 100% for CI, but this was not statistically significant ( P = 0.51). Several additional case series and pilot studies have also shown benefit of PET‐MRI in evaluating STS …”
Section: Applications Of Pet‐mri In Oncologic Musculoskeletal Diseasementioning
confidence: 97%
“…The advent of hybrid positron emission tomography/magnetic resonance (PET/MR) using either 2‐deoxy‐2‐[fluorine‐18]‐fluoro‐D‐glucose (18F‐FDG) or 68gallium‐labeled‐prostate specific membrane antigen (68Ga‐PSMA) systems provide an opportunity to characterize a soft tissue mass of interest as benign or malignant using its anatomic and metabolic imaging characteristics, while simultaneously performing local as well as whole‐body staging. At this time, there is limited clinical experience on the utility of PET/MR on the evaluation of a musculoskeletal soft tissue mass at presentation, although quantitative PET/MR systems performed using DWI/ADC mapping enable quantitative voxel‐based measurement of standard uptake values (SUV) and ADC values synchronously . In 29 patients with sarcoma, 18F‐FDG PET/MR was comparable to conventional imaging (CT and MR) for initial sarcoma staging .…”
Section: Future Directionsmentioning
confidence: 99%